Anti- or pro-proliferation – Conditional options for TGF-α and cetuximab in head and neck squamous cell carcinoma. Issue 1 (January 2015) - Ekblad, Lars; Welinder, Charlotte; Kjellén, Elisabeth; Brun, Eva; Wennerberg, Johan
Summary Objectives Cetuximab is an epidermal growth factor receptor (EGFR)-targeting drug that has shown effects in head and neck squamous cell carcinoma (HNSCC). The effects are, however, small and have mainly been proven in a subset of patients, and the cost-effectiveness has been questioned. For this reason, we need to know more about the basic mechanisms controlling the effect of EGFR signalling on tumour growth. Materials and methods We investigated the effect of the EGFR ligand transforming growth factor alpha (TGF-α) and cetuximab, alone and in combination, on HNSCC cell lines, measuring proliferation and the activity of intracellular signalling pathways. Results In line with previous reports we found the majority of the cell lines to be growth-inhibited by TGF-α. Surprisingly, two of the cell lines, which were more thoroughly investigated, were either growth-inhibited or stimulated by both cetuximab and TGF-α, depending on the presence or absence of the other substance. We also present data indicating the existence of two different receptor activities emanating from the EGFR protein. Conclusion We therefore show that TGF-α can have both growth-stimulating and growth-inhibiting effects in the same cell line and that EGFR-targeting drugs can be similarly double-edged. The implication for such drugs is that the micro-environment within a tumour, and possibly within portions of a tumour, may influence the growth-inhibiting effect of the drug. There may also be important implications for our understanding of EGFR signalling and its influence on growth and development.